The biological impact of deuterium and therapeutic potential of deuterium-depleted water - Qu, Jiao; Xu, Yufei; Zhao, Shuang; Xiong, Ling; Jing, Jing; Lui, Su; Huang, Juan; Shi, Hubing (Frontiers in Pharmacology, 2024)
Since its discovery by Harold Urey in 1932, deuterium has attracted increased amounts of attention from the scientific community, with many previous works aimed to uncover its biological effects on living organisms. Existing studies indicate that deuterium, as a relatively rare isotope, is indispensable for maintaining normal cellular function, while its enrichment and depletion can affect living systems at multiple levels, including but not limited to molecules, organelles, cells, organs, and organisms. As an important compound of deuterium, deuterium-depleted water (DDW) possess various special effects, including but not limited to altering cellular metabolism and potentially inhibiting the growth of cancer cells, demonstrating anxiolytic-like behavior, enhancing long-term memory in rats, reducing free radical oxidation, regulating lipid metabolism, harmonizing indices related to diabetes and metabolic syndrome, and alleviating toxic effects caused by cadmium, manganese, and other harmful substances, implying its tremendous potential in anticancer, neuroprotective, antiaging, antioxidant, obesity alleviation, diabetes and metabolic syndrome treatment, anti-inflammatory, and detoxification, thereby drawing extensive attention from researchers. This review comprehensively summarizes the latest progress in deuterium acting on living organisms. We start by providing a snapshot of the distribution of deuterium in nature and the tolerance of various organisms to it. Then, we discussed the impact of deuterium excess and deprivation, in the form of deuterium-enriched water (DEW) and deuterium-depleted water (DDW), on living organisms at different levels. Finally, we focused on the potential of DDW as an adjuvant therapeutic agent for various diseases and disorders.